Lessons from patient-specific 3D models of the cardiac chambers after the Mustard operation. - Chapron,J; Hosny,H; Torii,R; Sedky,Y; Donya,M; Yacoub,MH (Global Cardiology Science and Practice, 2013)
The recent ability to create detailed 3D models of the atrial and ventricular chambers using CT, MRI and rapid prototyping offers unique opportunities to study the size and shape of the different cardiac chambers both before and following operation for complex cardiac anomalies. We here describe the techniques for creating detailed 3D models of the heart and demonstrate the utility of these techniques in a patient studied after the Mustard operation. This can give important insights into the changes in size and shape of the different chambers and the patterns of blood flow from the pulmonary and systemic veins to the 'appropriate' ventricle. This information in turn could be extremely helpful in understanding and optimizing the overall hemodynamic function after the Mustard operation.